THE USE OF ECONOMICMATHEMATICAL METHODS TO EVALUATE THE PERFORMANCE OF THE CONSOLIDATED GROUP OF INTERDEPENDENT ORGANIZATIONS - Natalia A. Kondrashova (Статистика и экономика, 2016)
This article deals with the methodologicalaspects of evaluation of activities of the Russian interdependent organizations which usethe mechanism of the consolidated budgetpayments in connection with the introductionin the Russian legislation the concept of aconsolidated group of taxpayers («CTG»).For adoption by the organizations decisionon the establishment of CTG in this paperthe author proposed a preliminary analysis ofthe results of the operation have already created CTG using economic and mathematicalmethods. Deﬁ ned economic-mathematical model of calculation of the consolidation differences, the practical examples of calculations of the coefﬁcients of relationshipappropriate indicators.